(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
This article explores the role of national identity and the influence of mass media on social consciousness. It emphasizes that media plays a crucial part in shaping perceptions of national uniqueness by presenting historical figures and events in various interpretations, which may either strengthen intercultural harmony or provoke conflicts. The article also examines how migration, multiculturalism, and globalization impact national identity in the global media landscape. Through examples from films, news outlets, and documentaries, it highlights that media representations of national and religious identities can often lead to social tensions. In conclusion, national and cultural identity is described as a cultural rather than biological phenomenon, with media bearing significant responsibility for its formation and preservation.